WHERE IS KENYA BEING HEADED TO? EMPIRICAL EVIDENCE FROM THE BOX-JENKINS ARIMA APPROACH - NYONI, Thabani (Theoretical and Practical Research in Economic Fields; Vol 10 No 2 (2019): TPREF, Volume X, Issue 2(20), Winter 2019, 2019)
Using annual time series data on GDP per capita in Kenya from 1960 to 2017, the study analyzes GDP per capita using the Box – Jenkins ARIMA technique. The diagnostic tests such as the ADF tests show that Kenyan GDP per capita data is I (2). Based on the AIC, the study presents the ARIMA (3, 2, 1) model. The diagnostic tests further show that the presented parsimonious model is stable and reliable. The results of the study indicate that living standards in Kenya will improve over the next decade, as long as the prudent macroeconomic management continues in Kenya. Indeed, Kenya’s economy is growing. The study offers 3 policy prescriptions in an effort to help policy makers in Kenya on how to promote and maintain the much-needed growth.